2021
DOI: 10.1371/journal.pone.0246301
|View full text |Cite
|
Sign up to set email alerts
|

Diphtheria outbreak in Jakarta and Tangerang, Indonesia: Epidemiological and clinical predictor factors for death

Abstract: Background In 2017, a diphtheria outbreak occurred in several provinces in Indonesia. The aim of this study was to identify predictors of mortality outcome of pediatric patients with clinical diphtheria. Methods A retrospective cohort study was conducted using patient medical records at five referral hospitals in the Province of Jakarta and one in Tangerang District, Banten Province during January 2017 to 31 August 2018. All children in the age group of 1–18 years old discharged with diagnosis of clinical di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 20 publications
(36 reference statements)
2
16
0
1
Order By: Relevance
“…Our findings showed a notable rise in the number of diphtheria cases during the months between October 2017 and January 2018, which are considered winter months. This finding is consistent with the findings of previous studies in Yemen and Indonesia [ 11 , 13 , 14 ]. A decline in the cases after the peak started in February and continued until August 2018.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our findings showed a notable rise in the number of diphtheria cases during the months between October 2017 and January 2018, which are considered winter months. This finding is consistent with the findings of previous studies in Yemen and Indonesia [ 11 , 13 , 14 ]. A decline in the cases after the peak started in February and continued until August 2018.…”
Section: Discussionsupporting
confidence: 94%
“…Diphtheria outbreaks often occur because of low childhood vaccination, as well as lack of booster vaccinations for older children and adults [ 17 ]. This supports our findings that most affected cases were unvaccinated, which is consistent with the findings of previous studies in India and Indonesia reporting that mortality occurred in more than 70% of patients who did not receive complete immunization [ 14 , 18 ]. Our study confirms that raising immunity levels in the population through vaccination remains a critical tool for diphtheria control.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, as an alarming symptom, almost 50% of the cases exhibited bull neck as a toxic sign affecting prognosis (29). Furthermore, although only three cases (7.5%) had myocarditis, awareness is required since it is correlated with fatal cases (7,30). All cases with myocarditis complications passed away in this study.…”
Section: Discussionmentioning
confidence: 60%
“…Some studies have presented a microbiological and clinical overview of diphtheria (7,13); however, an analysis of laboratory-confirmed cases is rare. Some previous studies have also illustrated diphtheria-confirmed cases with small sample sizes; however, some others have presented a partial overview in separated aspects (12,14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation